Development and optimization of simultaneous determination of fat soluble vitamins by liquid chromatography tandem mass spectrometry. (August 2020) - Ertugrul, Sebla; Yucel, Cigdem; Sertoglu, Erdim; Ozkan, Yalcin; Ozgurtas, Taner
Highlights: Fat-soluble vitamins (A, D, E and K) detection. Developed and validated a sensitive and specific LC–MS / MS method. Short sample preparation and analysis time. Simultaneous analysis of fat-soluble vitamins. Useful method for clinical purposes by replacing immunoassay and HPLC methods. Abstract: Objective: Fat-soluble vitamins (A, D, E and K) are isoprene derived apolar molecules. While deficiencies of these vitamins have been associated with various diseases such as type 2 diabetes and cancer, high doses of Vitamin A and D can cause toxic effects. Accurate detection of serum levels of these vitamins have critical importance. In this study, it is aimed to develop and validate a sensitive and specific Liquid Chromatography Tandem Mass Spectrometry (LC–MS / MS) method that allows simultaneous analysis of fat-soluble vitamins. Materials and Methods: Serum samples were deproteinized with methanol and chromatographic separation of analytes were performed by LC–MS/MS system (Agilent Technologies 6420 Triple Quadrapole LC–MS), Agilent Pursuit PFP column (100 mm × 3.0 mm; 3.0 μm), in gradient mode using Mobile phase A (milli-Q+0.1 % formic acid) and Mobile phase B (Methanol+0.1 % formic acid). Ion scan was performed in MRM (multiple reaction monitoring) mode with positive ion selectivity in ESI ion source. Results: The retention times were 6.93 min, 6.94 min and 9.34 min while concentrations were linear in the ranges between 10−150 ng/mL, 3−90 μg /dL and 6−90 μg/mL for 25-hydroxy vitamin D3 (25−OHD3 ), Vitamin A and Vitamin E, respectively. Inter-day Coefficient Variation (CV%) values for Vitamin A, Vitamin E and 25−OHD3 were; 9.08 %, 9.85 % and 3.07 % and intra-day CV% values were; 2.98 %, 5.05 % and 5.01 %. LOD and LOQ results were 2.11 μg/dL and 3.50 μg/dL for Vitamin A; 1.71 μg/mL and 2.45 μg/mL for Vitamin E; 1.47 ng/mL and 2.50 ng/mL for 25−OHD3, respectively. Conclusion: In this study, a LC–MS/MS method that can analyze fat soluble vitamins in 13 min was developed and validated. This method will be useful for clinical purposes by replacing low specificity immunoassay methods and High Performance Liquid Chromatography (HPLC) methods that can not allow simultaneous analysis.